PENGARUH KOMPENSASI, KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI PT INTI HOSE JAYA PERKASA - Calvin; Syaifullah (SCIENTIA JOURNAL, 2022)
The purpose of this study is to examine the impact of Compensation, Leadership, and Work Environment towards employee performance. Population in this research contains all employees at PT Inti Hose Jaya Perkasa and all the members of the population were the sample. The collection’s data technique used questionnaire which was distributed using google form. The t test hypothesis test result shows that compensation has a positive sigificant effect toward employee performance with a t count > t table of 2.321 > 1.98157 and significance value 0.022 < 0.05, leadership has a positive significant effect toward employee performance with t count > t table of 4099 > 1.98157 and significance value of 0.000 < 0.05, the work environment has a positive significant effect toward employee performance with a t count > t table of 4.977 > 1.98157 and significance value of 0.000 < 0.050. Then the results of the F test shows that compensation, leadership and work environment simultaneously affect employee performance with a calculated F value > F table of 55.500 > 2.69 with a significance value of 0.000 < 0.050.